Manipulating magnetoelectric properties by interfacial coupling in La0.3Sr0.7MnO3/Ba0.7Sr0.3TiO3 superlattices - Haizhong Guo (Nature Portfolio, 2017)
Abstract Artificial superlattices constructed with ferromagnetic La0.7Sr0.3MnO3 layer and ferroelectric Ba0.7Sr0.3TiO3 layer were designed and fabricated on SrTiO3 substrates. An epitaxial growth with sharp interfaces between La0.7Sr0.3MnO3 and Ba0.7Sr0.3TiO3 layers was confirmed by scanning transmission electron microscopy and x-ray diffraction. An unambiguous charge transfer involving an electron transferring from the La0.7Sr0.3MnO3 layers to Ba0.7Sr0.3TiO3 layers (Mn3+→Mn4+; Ti4+→Ti3+) across the interface were resolved by electron energy loss spectra analysis. These observations are attributed to the possible modification in the stereochemistry of the Ti and Mn ions in the interfacial region. The out-of-plane lattice parameter, Curie temperature, and magnetoresistance are strongly affected by the thicknesses of the La0.7Sr0.3MnO3 and Ba0.7Sr0.3TiO3 layers. Huge magnetoresistance subsisting to low temperature was also observed in the La0.7Sr0.3MnO3/Ba0.7Sr0.3TiO3 superlattices. All spectral changes identified at a nanometer scale and their potential effect on the degradation of magnetic and transport properties at a macroscopic level. These findings highlight the importance of dependence on sublayer thickness, illustrating the high degree of tenability in these artificially low-dimensional oxide materials.